Effect of Working Capital Turnover, Capital Structure, Company Size, and Sales Growth on Profitability - Lina Puji Lestari; Sri Wahyuni; Novi Dirgantari; Selamet Eko Budi Santoso (Journal of Finance and Business Digital, 2022)
Profitability is very important because it can affect investors' preferences about the company. This study aims to analyze and prove empirically the effect of working capital turnover, capital structure, company size, and sales growth on profitability. The population in this study are property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The sampling technique used purposive sampling method and obtained a sample of 29 companies that met the criteria. The analysis technique used is multiple regression analysis and uses quantitative methods. The results of this study indicate that the working capital turnover variable has no effect on profitability. The capital structure variable has a negative effect on profitability. Variable company size and sales growth have a positive effect on profitability. This research provides a scientific contribution in the form of insight into some of the influence of profitability factors in property and real estate sector companies listed on the Indonesia Stock Exchange.